Solomon Islands : Economic Development Documents- Medium-Term Development Plan, 2016-20. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2016)
This report describes Solomon Islands' macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major source of financing. Solomon Islands' government Medium Term Development Plan (MTDP) 2016-20 sets out development programs and projects supporting the draft National Development Strategy (NDS) 2016-35 objectives. The MTDP is rolling out five-year plan, revised annually, comprising development programs and projects. The MTDP effectively addresses key issues of the economy which are as follows: existing poverty situation and trends, factors influencing poverty, strategies and policies for poverty reduction, fiscal and debt framework, and safety nets and risk mitigation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet